Hydrogen and syngas generation from gasification of coal in an integrated fuel processor - Chowdhury, S. (Trans Tech Publications Ltd, 2014)
Hydrogen is a clean and new energy carrier to generate power and effectively turned out through the gasification of organic material such as coal. The main objective of this manuscript is to present an analysis of the coal gasification for the generation of high-purity hydrogen in a lab-scale fixed-bed downdraft gasifier. Better understanding of the rank, formation, structure, composition and calorific value, and method of analysis of the material is crucial for the proper utilization of these resources requirements. Traditionally the quality of the coal samples has been determined by their physical and proximate analysis such as bulk density, free swelling index, gross calorific value, sulfur content, moisture content, fixed carbon, volatile matter, and ash content. In this study, coal is partially oxidized and ultimately converts into hydrogen rich syngas (CO and H2). As well, approximately 220 kg hâ1of coal would be gasified at 673 â 1073 K and 46.2 atm with the reactor volume of 0.27 m3 to obtain approximately 3.8Ã105 kcal hâ1of thermal energy during over 67 syngas generation with the generation of 110 kW electrical powers. Â© 2014 Trans Tech Publications, Switzerland.